Enhanced production of human Cytochrome P450 2C9 by Escherichia coli BL21(DE3)pLysS through the novel use of grey relational analysis and Plackett-Burman design - Hao, Da C; Zhu, Pan H; Yang, Sheng L; Yang, Ling (World journal of microbiology & biotechnology, 2007)
Cytochrome P450 (CYP, P450) 2C9 is one of three human microsomal CYPs in subfamily 2C that contribute extensively to the hepatic metabolism of therapeutic drugs. The enhancement of recombinant CYP2C9 expression of a transformed E. coli strain is essential for the development of an efficient large-scale bioprocess. The recombinant CYP2C9 production is influenced by various factors, especially the medium components. The aim of this study is to optimize the culture medium of the recombinant E. coli, to determine the influence order of 11 factors, and to improve the yield of heterologously expressed CYP2C9. Plackett-Burman (PB) design, a statistical methodology, was used to screen 11 nutrients and medium components for the production of human CYP2C9 from E. coli BL21(DE3)pLysS harboring plasmid pCW2C9dH in aerobic shaking flask cultures. The experimental data were subject to statistical analysis for calculating the regression coefficients. The matrix of PB design was also used to construct the series that is needed for grey relational analysis (GRA), an approach totally different from traditional statistical analysis used to calculate the relational grade between two sequence data, to determine the influence priority of 11 parameters. Influence priority: glycerol > δ-ALA > IPTG = ampicillin > chloramphenicol = inoculum density > peptone > thiamine > trace elements > NH₄Cl > MgSO₄. The coefficient for the individual factor estimated from PB design agrees the conclusion of GRA. This is the first report that combined two powerful analysis methods for the enhanced production of recombinant protein.